Nonverbal communication and narrative literature: Genesis 39 and the Ruth novella - Kruger, Paul Albertus (Biblische Notizen, 2009)
This contribution draws the attention anew to the relative neglect of the phenomenon of nonverbal communication in Hebrew Bible encyclopaedias. After a short survey of the most important studies published thus far on this topic in the fields of ancient Near Eastern and Hebrew Bible studies, a passage in the Joseph story (Gen 39:12) and some indicators of the nonverbal category “proxemics” (spatial behaviour) in the Ruth novella are selected as cases in point. This illustrates what interesting perspectives may be gained if the explicit focus is directed to some of these (apparently insignificant) nonverbal-symbolic details in these narrative accounts.